An Exploratory Study Of Language Attitudes Among Second Cycle Students In The New Juaben Municipality Of Ghana (International Journal of Technology and Management Research, 2020)
This paper is concerned with the relationship between attitude and behaviour in language. Adolescent male and female subjects were recorded and index-scores of their linguistic behaviour compared to their assessment of in- group members in a verbal-guise attitude experiment, and to their attitudes concerning language usage in a questionnaire. It was hypothesized that male subjects' language would be closer to the vernacular, and that they would also express more positive attitudes towards in-group members than would female subjects. However, no significant correlation between attitude and behaviour was found in the quantitative analysis, but results from the attitude-questionnaire support our hypothesis: male subjects have more vernacular features in their language and also express more genuinely positive attitudes towards the local vernaculars than do female subjects. Finally, methodological and theoretical implications of these results are discussed, emphasizing the importance of using eclectic approaches in future research on attitude-behaviour relations in language.Keywords: Language attitudes; attitude-behaviour relations